Pengaruh Adversity Quotient terhadap Kinerja Perawat dengan Motivasi Kerja sebagai Variabel Mediasi (Studi di RSUD Ngudi Waluyo Wlingi) - Utami, Endah Woro; Dewanto, Aryo (Universitas Brawijaya, Indonesia, 2013)
This research purposed to find the influence of Adversity Quotient to influence nurse performance in document processing of nursing care standard at RSUD Ngudi Waluyo Wlingi. The research design was analitic descriptive survey, using cross sectional study, cluster random sampling on 76 respondents (nurses). Tools of research were Adversity Quotient questionnaire, motivation questionnaire, and nurse care standard document study. Data was analized by using path analysis. The result was Adversity Quotient indirectly influence nurse job performance in documenting nursing care standard through motivation in RSUD Ngudi Waluyo Wlingi.